PENGARUH MEDIA MYSTERY BOX TERHADAP KEMAMPUAN MENULIS EKSPOSISI SISWA KELAS IV UPT SD NEGERI 87 TAMANROYA KECAMATAN. GALESONG UTARA, KABUPATEN. TAKALAR - Safitri Matwear; Syekh Adiwijaya Latief; Muhammad Saeful (STKIP Subang, 2025)
This research is motivated by the lack of use of learning media in the learning process, learning activities are still focused on the teacher, students are less focused on learning and often complain of boredom in participating in learning. This study aims to improve the exposition writing skills of grade IV students of UPT SD Negeri 87 Tamanroya. Through the Mystery Box learning media. This study aims to determine the effect of Mystery Box media on the exposition writing skills of grade IV students of UPT SD Negeri 87 Tamanroya. This research is a quantitative study using an experimental method with a one-group pre-test and post-test design. The data collection techniques used are observation, testing, and documentation. The data analysis technique was carried out using SPSS Statistics version 25. The data in this study were analyzed using descriptive statistical analysis techniques and inferential statistical analysis. The results of the study showed that there was an effect of Mystery Box media on the writing skills of grade IV students of UPT SD Negeri 87 Tamanroya. This was shown in the pretest with an average value of 60.2. While in the posttest it increased with an average value of 90.4. The results of the t-test analysis on the influence of Mystery Box media on student learning outcomes showed that the significance value obtained was good, namely the influence of Mystery Box media on the ability to write exposition texts (Sig = 0.000) was smaller than the specified alpha value of 0.05 (0.000 <0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of Mystery Box media on the ability to write exposition texts of grade IV students of UPT SD Negeri 87 Tamanroya, Takalar Regency.Keywords: Writing Ability, Exposition, Mystery Box Media.